Insights to vertical jumping from computer simulations - Challis, J. H.; Domire, Z. J. (Movement & Sport Sciences - Science & Motricité, 2015)
Maximum vertical jumping has served as a useful tool for examining musculoskeletal coordination. This review is to present the results of three simulation studies of maximal human vertical jumping. The model is a direct dynamics muscle model driven model which uses optimization to simulate maximum jumps in the sagittal plane. The first study demonstrates how a model can be used to guide technique modification to optimize subject performance. The second study illustrates how muscle properties dictate jumping performance. Finally, the third study explains how armswing influences jump performance. Models are by definition flawed representations of the systems they emulate, but despite this they provide a powerful tool, and a useful adjunct to experimental studies, for the examination of musculoskeletal coordination.